2021
DOI: 10.1039/d1ra05199g
|View full text |Cite
|
Sign up to set email alerts
|

pH sensing and bioimaging using green synthesized carbon dots from black fungus

Abstract: Carbon dots derived from black fungus were prepared and applied as a pH sensor for real water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The images of both cell lines revealed that the CNPs have potential for bioimaging, since they had a zeta potential value of −24.10 (cationic) and a pH of 7.2, demonstrating their ability to penetrate into the cell membrane [ 47 , 48 , 49 , 50 ]. However, further investigations on the uptake of CNPs by individual cell organelles and nuclei are still required.…”
Section: Resultsmentioning
confidence: 99%
“…The images of both cell lines revealed that the CNPs have potential for bioimaging, since they had a zeta potential value of −24.10 (cationic) and a pH of 7.2, demonstrating their ability to penetrate into the cell membrane [ 47 , 48 , 49 , 50 ]. However, further investigations on the uptake of CNPs by individual cell organelles and nuclei are still required.…”
Section: Resultsmentioning
confidence: 99%
“…Several environmental and biological processes are influenced by pH, and changes in pH could reveal pollutants or diseases. CDs derived from black fungus demonstrated changes in fluorescence in solution in response to pH due to protonation-deprotonation of the surface functional groups [31]. As shown in figures 8(a) and (b), the fluorescence intensity increased as the pH increased from 1 to 4, and then gradually decreased in a linear fashion to pH 13.…”
Section: Ph Sensing Using Carbon Dotsmentioning
confidence: 91%
“…Furthermore, from ecological safety and sustainability perspectives, the synthesis of CDs from natural resources could mitigate environmental pollution and assist with waste management by repurposing agricultural waste into valueadded products. Other natural precursor materials include black fungus [31], bagasse, coffee grounds, banana juice, potatoes, leaves, palm shell powder, orange juice, vegetable waste and soybean juice, among others [32][33][34][35][36].…”
Section: Synthesis Of Carbon Dots From Organic Precursorsmentioning
confidence: 99%
“…The absorption peak at 280 nm can be attributed to a π-π* leap in the aromatic sp2 structural domain and has strong absorption, including C=C and C=O bonds. The C=O bond can also undergo an n-π* leap, which requires less energy and can have less strong absorption in the near-UV or visible region, while the absorption peak at 430 nm near the long-wave region is attributed to a red shift phenomenon where the maximum absorption peak is shifted towards the long-wave direction due to the influence of the substituent or solvent [38]. Polar solvents can shift the UV absorption peak in the long-wavelength direction.…”
Section: Optical Properties Of N-cqdsmentioning
confidence: 99%